The Interest of the Young Generation in Coffee Shop Entrepreneurship in Bukit District, Bener Meriah Regency, Aceh - Arman, Iman; Pranata, Yuda; Novita, Aisar (Kadiri University - Faculty of Agriculture, 2024)
The Bukit District in the Bener Meriah Regency of Aceh Province presents a promising landscape for coffee shop entrepreneurship, given its strategic location and substantial foot traffic. This study delves into the inclination towards entrepreneurship among the youth in Bukit District and explores the factors that shape this inclination. Conducted from March 6 to May 18, 2023, the research employed a blend of observations, interviews, and questionnaires to gather data, with SPSS 24 for Windows utilized for analysis. Findings reveal a remarkable 77.33% interest level among the younger generation towards coffee shop entrepreneurship in Bukit District. This interest is primarily driven by factors such as education, income, experience, capital, family environment, and community dynamics. Noteworthy influences include income, capital availability, and the community environment, which significantly impact the inclination towards entrepreneurship. Conversely, education level, prior experience, and family environment exhibited no significant effect on this inclination. The results underscore the importance of economic factors such as income and access to capital, alongside social and environmental contexts, in shaping entrepreneurial aspirations among the youth in Bukit District. Understanding these dynamics can inform policies and initiatives aimed at fostering entrepreneurship in the region. This study contributes valuable insights for stakeholders interested in promoting economic development and harnessing the entrepreneurial potential of coffee shop ventures in Bukit District and similar settings.